STRATEGY TO OPTIMIZE ORIGIN REVENUE IN THE PARKING FIELD AT THE TRANSPORTATION SERVICE OF PANGANDARAN DISTRICT - Audina, Liska; S. Munir , S. Munir; Henriyani , Etih (Journal Education and Government Wiyata, 2023)
Based on the results of initial observations, it is known that the attainment of local revenue sourced from parking fees has not been able to reach the targets set, this is evidenced by data on achieving the PAD targets from parking fees in 2017-2019 which were not achieved according to the target. The objectives of this study are as follows: 1) To find out the strategy for optimizing regional original income in the Parking Sector at the Pangandaran Regency Transportation Service. 2) To find out the obstacles to the strategy of optimizing regional original income in the Parking Sector at the Pangandaran Regency Transportation Service. 3) To find out the efforts to overcome the obstacles to optimizing local revenue strategies in the Parking Sector. The method used in this research is descriptive analysis. Informants as many as 10 people. Data collection techniques are library research, field studies (observations and interviews) and documentation. The author uses qualitative data analysis techniques through data processing from interviews and observations to draw conclusions so that they can answer problems in research. Based on the results of the study that: 1) The strategy of optimizing regional original income in the parking sector is not optimal according to the opinion of Djalil (2014: 297) this is evidenced by the lack of improvement of the potential parking levy database and the lack of review of provisions related to types and rates of parking fees, Besides that, there is a lack of intensification of the sources of parking fee receipts by exploring the sources of parking fee receipts. 2) The obstacles are due to the lack of improvement on the database of potential parking fees because the involvement of all parties is still lacking in planning the collection of parking fees, besides that the review of various provisions in determining fee rates is still not carried out routinely. 3) Efforts to overcome obstacles in implementing the strategy of optimizing Local Revenue in the Parking Sector at the Pangandaran Regency Transportation Service, this is done by seeking to improve the potential parking levy database by involving all parties in planning parking retribution collection, in addition to carrying out assessment of the various provisions in determining retribution rates so as to achieve parking retribution targets. Efforts are made through routine technical assistance for retribution collection officers as well as increasing public awareness in paying parking fees.